Complementary & alternative medicine for prostate and urologic health - Moyad, Mark A. (Springer New York, 2014)
Complementary & Alternative Medicine for Prostate and Urologic Health is designed to capture and clinically review the comprehensive database of clinical research articles that support and do not support the utilization of a variety of dietary supplements and other complementary medicines that physicians are exposed to in their daily practice.  This is a critical distinction between this book and any other Complementary & Alternative Medicine (CAM) books published to date. Each section of the book provides an easy to reference guide into the topic of interest for the individual that works in urology.  The various sub-specialty groups in urology are adequately represented, which allows for a physician to rapidly and thoroughly investigate their topic of interest regardless of whether it is fertility, bladder cancer, or prostate disease.  Rather than having to sort through the now thousands of articles published yearly on CAM in medicine, this volume focuses first on the specialty and secondarily how it compares to the overall CAM literature.  Each chapter includes a summary page that will allow the physician a rapid review of the subject with a patient, colleague or student.     The practical nature of this book in urology also cannot be overstated.  Chapters include a general overview of the CAM agent, whether or not it has data in medicine and urology, and a list of potential drug interactions and specific clinical scenarios where it can be utilized or discouraged in the specialty.  Complementary & Alternative Medicine for Prostate and Urologic Health represents a gold standard text for use in teaching, not only for the students interested in the urologic field but for all current urologic health providers.